Phylogeny-Directed Search for Murine Leukemia Virus-Like Retroviruses in Vertebrate Genomes and in Patients Suffering from Myalgic Encephalomyelitis/Chronic Fatigue Syndrome and Prostate Cancer - Jonas Blomberg; Ali Sheikholvaezin; Amal Elfaitouri; Fredrik Blomberg; Anna Sjösten; Johan Mattson Ulfstedt; Rüdiger Pipkorn; Clas Källander; Christina Öhrmalm; Göran Sperber (Advances in Virology)
Gammaretrovirus-like sequences occur in most vertebrate genomes. Murine Leukemia Virus (MLV) like retroviruses (MLLVs) are a subset, which may be pathogenic and spread cross-species. Retroviruses highly similar to MLLVs (xenotropic murine retrovirus related virus (XMRV) and Human Mouse retrovirus-like RetroViruses (HMRVs)) reported from patients suffering from prostate cancer (PC) and myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) raise the possibility that also humans have been infected. Structurally intact, potentially infectious MLLVs occur in the genomes of some mammals, especially mouse. Mouse MLLVs contain three major groups. One, MERV G3, contained MLVs and XMRV/HMRV. Its presence in mouse DNA, and the abundance of xenotropic MLVs in biologicals, is a source of false positivity. Theoretically, XMRV/HMRV could be one of several MLLV transspecies infections. MLLV pathobiology and diversity indicate optimal strategies for investigating XMRV/HMRV in humans and raise ethical concerns. The alternatives that XMRV/HMRV may give a hard-to-detect “stealth” infection, or that XMRV/HMRV never reached humans, have to be considered.